EU defence policy needs strategy: Time for political examination of the CSDP's reform objectives - Rosa Beckmann; Ronja Kempin (Stiftung Wissenschaft und Politik (SWP), 2017)
The European Union's Common Security and Defence Policy (CSDP) has made great strides since publication of the EU Global Strategy (EUGS) in June 2016. Tectonic shifts in the geopolitical environment and within the Union itself have led the states and the Commission to launch a string of initiatives seeking to expand the EU's strategic autonomy in security and defence. These efforts can only be sustainable if the projects involved are placed on a long-term footing and a process of reflection about the orientation of the CSDP begins. Year two of EUGS implementation should be used to initiate steps in that direction.
Keywords: 320